GARAP TARI KETHEK OGLENG DI DESA NGAMBARSARI, KARANGTENGAH KABUPATEN WONOGIRI - Eka Nurpilang; Hadi Subagya (Institut Seni Indonesia Surakarta, 2021)
This article is the result of research from ideas to reveal the creativity of the Kethek Ogleng Dance in Ngambarsari village, Karangtengah sub-district, Wonogiri district, namely the Bawang Sari Cultural Community (BBS) with reference to the artistry of community leaders. The problem that was revealed was working on the Kethek ogleng dance in N Gambarsari village, Karangtengah sub-district, Wonogiri district. This research is qualitative in nature with data collection strategies through observation, interviews, and literature studies. The form theory uses Suzane K Langer's statement which is supported by Soemandyo Hadi's concept of form and the main concept of